241 Intrathecal antisense oligonucleotide delivery in HD: experience from RG6042 programme and best practice considerations. Issue 6 (27th May 2022) - Leavitt, Blair; Wild, Edward; Bang, Jee; Smith, Anne; Schlegel, Valerie; Schobel, Scott; Nicotra, Alessia; Landwehrmeyer, Bernhard; Tabrizi, Sarah; ,
Abstract : Intrathecal administration involves the introduction of a drug substance into the subarachnoid space of the spinal column through a needle inserted into the lower back via lumbar puncture (LP) or via a special device. This procedure is used when drugs cannot cross the blood-brain barrier. Once injected, drugs are distributed within the cerebrospinal fluid from which they can access target tissues in spinal cord and brain. We use the intrathecal route to deliver RG6042 (previously HTTRx), an investigational, huntingtin mRNA- targeting antisense oligonucleotide to patients with Huntington's disease (HD). Experience on intrathe- cal administration via LP has been gained in the RG6042 clinical development programme, including the double-blind, placebo-controlled, multiple ascending dose, Phase I/IIa study (NCT02519036 ) in 46 patients with early manifest HD and an open-label extension (NCT03342053 ) where patients received 120 mg RG6042 monthly or every other month in a 62-week treatment period (total procedures ≥400 in the programme to date). We will report on the experience with intrathecal drug delivery across these two studies and present information on suggested best practices in HD. Procedure-related videos will be shared, including use of spinal ultrasound. Finally, we will describe real-world considerations of implementing intrathecally delivered therapies in the clinical interface. alessia.nicotra@roche.com